Simulasi Pipa Transmisi Air Baku Dari Sumber Air Sungai Jurong 2 Ke PDAM Tirta Dharma Duri - Heriansyah Heriansyah; Siswanto Siswanto; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Waters demand in District of Mandau is a concern because of population growth and increasing water shortages in the dry season . Therefore, needed a new alternative source of raw water to meet water needs in District of Mandau deep water channel of a new raw water source required transmission pipelines to the water treatment plant. Then the required study of several alternative raw water transmission pipeline system. The results of this study can be concluded from the results of population projections obtained percentage of water services in 2013 amounted to 24 %, in 2017 amount 29 %, in 2022 amount 30 %, in 2027 amount 35%, in 2032 amount 53 %. Water demand planning used 4 alternate with 4 different discharge to increase the supply of raw water supply in District of Mandau which only amounted to 80 liters/sec. Simulation of the raw water transmission system for District of Mandau obtained is expected to be a guide in the planning pipeline for PDAM Tirta Dharma transmission Duri.Keywords: waters demand,PDAM, transmission system